Intermittent Energy Restriction for Weight Loss: A Systematic Review of Cardiometabolic, Inflammatory and Appetite Outcomes. Issue 3 (July 2022) - Wei, Xueting; Cooper, Ashley; Lee, Irene; Cernoch, Christine A.; Huntoon, Ginny; Hodek, Brandi; Christian, Hanna; Chao, Ariana M.
Current guidelines for obesity treatment recommend reducing daily caloric intake for weight loss. However, long-term weight loss continues to be an issue in obesity management. Alternative weight loss strategies have increased in popularity, such as intermittent energy restriction (IER), a type of eating pattern with periods of fasting alternating with unrestricted eating. The effects of IER on weight loss, cardiovascular risk factors, inflammation, and appetite are not clear. The purpose of this systematic review was to analyze short- (<24 weeks) and long-term (≥24 weeks) effects of IER on anthropometric, cardiometabolic, inflammatory, and appetite outcomes in adults with overweight/obesity. PubMed, CINAHL, Embase, and PsycInfo were searched from inception to July 2020. Human randomized controlled trials (RCTs) on IER with participants with a body mass index ≥25 kg/m 2 were included in this review. A total of 42 articles (reporting on 27 different RCTs) were included. In short-term studies, IER showed pre-to-post treatment improvements in eight of nine studies that assessed weight. Weight outcomes were sustained in the long-term. However, no significant long-term between group differences were observed in fat mass, other anthropometric, cardiometabolic, inflammatory, or appetite outcomes. Compared to continuous energy restriction (CER), IER showed no significant long-term differences in anthropometric, cardiometabolic, inflammatory, or appetite outcomes in included studies. More long-term studies are needed to assess the benefits of IER on health outcomes.